BUSINESS MODELS FOR SMES IN THE BEEF INDUSTRY: MARKET INTEGRATION AND SUSTAINABILITY STRATEGIES - Muhammad Wildan Firdaus; Lestari, Yetty Dwi (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2026)
This study examines the development of business models for Micro, Small, and Medium Enterprises (MSMEs) in the beef industry, with particular emphasis on market integration and sustainability strategies. The study adopts an integrative literature review approach to synthesize recent scholarly discussions on MSMEs, beef supply chains, business model development, digital transformation, and sustainability. The review draws on peer-reviewed publications indexed in Scopus and ScienceDirect from 2020 to 2025 and employs thematic synthesis to identify major patterns and conceptual linkages across the literature. The findings indicate that MSMEs play a strategic role in the beef industry as intermediaries in distribution, contributors to local price stability, and generators of employment; however, their performance remains constrained by fragmented supply chains, weak market integration, limited technological adoption, and restricted access to strategic partnerships. The review further shows that adaptive business models are strengthened through the integration of value creation, value delivery, and value capture, supported by digitalization, vertical coordination, and collaborative networks. In addition, sustainability-oriented approaches grounded in resource optimization, dynamic capabilities, and sustainable value chain thinking are consistently associated with greater business resilience and long-term competitiveness. By integrating these perspectives, this study offers a conceptual understanding of how MSMEs in the beef industry can strengthen competitiveness and adaptability in an increasingly complex food-system environment. The study also provides practical insight for the development of more integrated and sustainable MSME strategies in the agribusiness sector.